HUBUNGAN ANTARA HIPERTENSI DAN KADAR KOLESTEROL DENGAN PENYAKIT JANTUNG KORONER (PJK ) DI RSUD BESEMAH PAGAR ALAM - Fika Minata; Megi Irawanza (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Coronary heart disease is a narrowing of the coronary arteries due to plaque accumulating in the innerwalls of the coronary arteries, blood vessels that function to supply oxygen, and food substances to theheart muscle. This study aims to determine the relationship between hypertension and cholesterol levelswith coronary heart disease. This research was carried out by taking medical record data in patients withCHD in the Besemah Pagar Alam Hospital in 2017, namely 45 people. This research is an analyticalsurvey with a cross sectional approach, in the sense of taking Independent Variable data (hypertensionand cholesterol levels) and Dependent Variables (Coronary Heart) carried out simultaneously. In thisstudy respondents who were positive for coronary heart disease were 27 respondents (60%) out of 45respondents. From the chi-square statistical test obtained (p value = 0.01 <? 0,05 stated that there was arelationship between hypertension and coronary heart disease and there was a correlation betweencholesterol levels and coronary heart disease, where it was obtained (p value = 0.038) smaller than ? 0The conclusion of this study is that there is a significant relationship between hypertension and coronaryheart disease and there is a significant relationship between cholesterol levels and coronary heartdisease.The suggestion of this study is to provide quality services and provide information to thecommunity by means of counseling so that people know how how to prevent coronary heart disease